GREEN ROOF SYSTEMS AS A SUSTAINABLE URBAN SOLUTION: PROSPECTS FOR APPLICATION IN UZBEKISTAN’S ARID CLIMATE - Hamidova Mohigul Hayotovna; Vohidov Shakhzod Kenjayevich (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This study investigates the feasibility and advantages of green roof systems as an ecological and architectural response to the challenges posed by urbanization and climate change in Uzbekistan. With increasing temperatures, heat island effects, and limited green spaces in major cities, green roofs offer a multifunctional solution—improving building insulation, reducing stormwater runoff, and enhancing air quality. The article explores international examples, analyzes local climatic constraints, and provides strategic recommendations for integrating green roofing into Uzbekistan’s construction sector.